Assessing the Costs and Benefits of Collective Bargaining – the Potential Use of Costing - Levine, Gilbert (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1973)
This paper presents the union point of view on collective bargaining costing.